Prevalence and antibiotic resistance of (Streptococcus equi) from nasal cavity of healthy equines - Pansani, Augusto Marsola; Gatto, Igor Renan Honorato [UNESP]; Frias, Danila Fernanda Rodrigues; Kozusny-Andreani, Dora Inés (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2016)
Strangles is a disease of the respiratory tract of horses caused by Streptococcus equi. The disease has high morbidity and low lethality, and produces economic losses due to low performance and high cost treatment. This research focused on evaluate antibiotic resistance of Streptococcus equi from the nasal cavity of healthy horses from the region Fernandópolis - São Paulo. Fifty (50) mongrel healthy horses, ageing from twelve to twenty four (12-24) months were used. Samples from the nasal cavity of each animal were obtained using sterile swabs and after were cultured on blood agar base plus 5[%] defibrinated sheep blood. Plates that showed mucous colonies and ß - hemolytic were tested using Gram stain method, the catalase test, and identified by the system API Rapid ID thirty-two 32 Strep. All isolates were analyzed by plate difusion. Sixty seven of the obtained isolates were Streptococcus equi subspecies equi and zooepidemicus. There was higher prevalence of S. subsp equi zooepidemicus (p < 0.001). Most isolates of S. equi subsp equi were antibiotical multiresistant with significant differences between different antibiotics (p < 0.005), whereas higher susceptibility was observed in isolated S. subsp equi zooepidemicus (p < 0.05). The results showed that both subspecies of Streptococcus equi are part of the normal flora of the nasal cavity of horses, and that they differ in susceptibility to antibiotics.
Prevalência e resistência a antibióticos de (streptococcus equi) da cavidade nasal de equinos hígidos no município de fernandopólis, são paulo, brasil